PENGEMBANGAN APLIKASI MAINTENANCE CAPACITY PLANNING MENGGUNAKAN SIMULASI MONTE CARLO - Dyandra Adya, Janitra
Maintenance is defined as a combination of activities that are required to maintain or restore an equipment or system so that it can perform its intended function. Because the maintenance load and the resource capacity are uncertain, an accurate forecast is needed to determine it. Maintenance capacity planning optimizes worker resource capacity to meet the forecasted maintenance load and minimizes the total cost. It is hard to find a capacity planning application that is free, easy to find, and has a stated calculation method on the market. Therefore, a capacity planning application that is easily accessible and used by the users is needed. By developing the application independently, innovation and selection of the calculation method can be done freely. In order to make the calculations closer to the real-life condition, the estimation of the maintenance load and resource capacity is carried out using a stochastic approach, specifically, Monte Carlo simulation. Then, capacity planning is continued with a deterministic approach, namely the Capacity Allocation Table and Linear Programming. The application, named “Maintenance Capacity Planning with Monte Carlo Simulation” was developed in Microsoft Excel. The optimization will be done using the add-in Solver feature available. The application has been verified and passed usability tests, so that it runs well, produces the correct solution, and is easy to use.